(untitled) (Castilla. Estudios de Literatura, 2022)
Review of the book Cuentos pendientes. Cuarenta y tres voces del cuento castellano y leonés del siglo XXI» (Valladolid, Castilla Ediciones, 2021), by José Ignacio García. The recent history of the short story in Castilla y León has been collected in anthological volumes that have meant a cleansing of the genre and the authors who have cultivated it. Among the most significant works, we find the study of José Luis Puerto, El cuento literario en Castilla y León (vols. I and II), from 2000 and 2002 for Edilesa. The growing interest it has aroused among authors, publishers and readers, made it advisable to take a new critical look at the Castilian and Leonese stories of recent decades, which would reflect the state of the matter at the beginning of the XXI century. Hence the need, interest and importance of a volume such as Cuentos pendientes. Cuarenta y tres voces del cuento castellano y leonés del siglo XXI, an anthology prepared by José Ignacio García that allows to publicize the extension of the genre and the most important authors not included, for reasons of age or dates of publication in the aforementioned anthologies, and their relations with the previous authors or with the same phenomenon in other Spanish regions.